2020
DOI: 10.1177/1055665620974562
|View full text |Cite
|
Sign up to set email alerts
|

Oronasal Fistula Incidence Associated With Vomer Flap Repair of Cleft Palate: A Systematic Review and Meta-Analysis

Abstract: Objectives: To determine the incidence of oronasal fistulas (ONF) associated with primary repair of the anterior palate using a single-layered, superiorly based, vomer mucoperiosteal flap. Design: A systematic review of MEDLINE, PubMed, Cochrane, and Web of Science databases using the keywords: “vomer flap” and “cleft palate repair” were carried out. A meta-analysis was performed using random effect modeling with stratified analysis by syndromic diagnosis, number of surgeons, and mean age. Main Outcome Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…It was observed that only three studies performed before 2010 could qualify during the two-stage scrutiny [ 72 , 112 , 113 ]. Among the journals, the highest number of papers (n = 30) was published in the Cleft Palate Craniofacial Journal (CPCJ) [ 21 , 35 , 46 , 47 , 48 , 49 , 63 , 65 , 66 , 76 , 86 , 92 , 94 , 100 , 101 , 115 , 116 , 121 , 123 , 125 , 128 , 137 , 140 , 142 , 146 , 150 , 152 , 155 , 161 , 162 ] followed by The Cochrane Library (n = 8) [ 9 , 16 , 68 , 88 , 92 , 93 , 100 , 106 ] and the International Journal of Oral and Maxillofacial Surgery (n = 7) [ 31 , 72 , 89 , 93 , 106 , 110 , 135 ]. There was diversity among the journals of different specialties that had published the SRs related to CLP ( Supplementary Material S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that only three studies performed before 2010 could qualify during the two-stage scrutiny [ 72 , 112 , 113 ]. Among the journals, the highest number of papers (n = 30) was published in the Cleft Palate Craniofacial Journal (CPCJ) [ 21 , 35 , 46 , 47 , 48 , 49 , 63 , 65 , 66 , 76 , 86 , 92 , 94 , 100 , 101 , 115 , 116 , 121 , 123 , 125 , 128 , 137 , 140 , 142 , 146 , 150 , 152 , 155 , 161 , 162 ] followed by The Cochrane Library (n = 8) [ 9 , 16 , 68 , 88 , 92 , 93 , 100 , 106 ] and the International Journal of Oral and Maxillofacial Surgery (n = 7) [ 31 , 72 , 89 , 93 , 106 , 110 , 135 ]. There was diversity among the journals of different specialties that had published the SRs related to CLP ( Supplementary Material S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics under this domain and their further categorization under various subdomains are detailed in Supplementary Material S4 . Among 15 SRs [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ], only 7 [ 135 , 136 , 141 , 142 , 143 , 144 , 145 ] had their protocol registered prior to conducting the study ( Figure 4 ). Meta-analysis was performed in 6 of the studies [ 133 , 140 , 142 , 143 , 144 , 145 ] ( Supplementary Material S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three (23.08%) patients with intraoral wounds and a palatal bone loss of about 7–8 mm developed an oronasal fistula with passage of water and food in the nasal cavity. These were closed within 15–20 days after primary surgery by a palatal mucoperiosteal flap [ 20 ]. All three healed without further incidents.…”
Section: Resultsmentioning
confidence: 99%
“…1,10,11 Still, anatomical descriptions are also frequently used in scientific literature. 12,13 The Pakistan Comprehensive Classification System however has not been cited yet to our knowledge in scientific literature besides the manuscript of the original author. 9 Sitzman et al published a study in 2018 that showed very limited inter-rater agreement for eight surgeons using the Pittsburgh classification system.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 10 , 11 Still, anatomical descriptions are also frequently used in scientific literature. 12 , 13 The Pakistan Comprehensive Classification System however has not been cited yet to our knowledge in scientific literature besides the manuscript of the original author. 9 …”
Section: Discussionmentioning
confidence: 99%